Income inequality around the world - Cappellari, Lorenzo; Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics, 2016)
Research in Labor Economics volume 44 contains new and innovative research on the causes and consequences of inequality and well-being of the workforce.